2022
DOI: 10.1038/s41467-022-32505-8
|View full text |Cite
|
Sign up to set email alerts
|

Mannose ameliorates experimental colitis by protecting intestinal barrier integrity

Abstract: Metabolite alteration has been associated with the pathogenesis of inflammatory bowel disease (IBD), including colitis. Mannose, a natural bioactive monosaccharide that is involved in metabolism and synthesis of glycoproteins, exhibits anti-inflammatory and anti-oxidative activities. We show here that the circulating level of mannose is increased in patients with IBD and mice with experimental colitis. Mannose treatment attenuates intestinal barrier damage in two mouse colitis models, dextran sodium sulfate (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 55 publications
6
61
0
Order By: Relevance
“…This would make D-mannose a highly effective seno-morphic as it modifies senescence risk. In line with this, mannose has been reported to protect against intestinal barrier dysfunction in a (young) mouse model of colitis (Dong et al, 2022). Moreover, we have recently reported that D-mannose prophylaxis led to a significant decrease in UTI incidence rate in patients with bTLT (Chiu et al, 2022).…”
Section: Discussionmentioning
confidence: 73%
“…This would make D-mannose a highly effective seno-morphic as it modifies senescence risk. In line with this, mannose has been reported to protect against intestinal barrier dysfunction in a (young) mouse model of colitis (Dong et al, 2022). Moreover, we have recently reported that D-mannose prophylaxis led to a significant decrease in UTI incidence rate in patients with bTLT (Chiu et al, 2022).…”
Section: Discussionmentioning
confidence: 73%
“…We investigated whether PNGase F is compatible with S-Trap sample preparation using RNase B as a model glycoprotein containing one known N-glycan that results in a characteristic mass shift upon cleavage. 51 PNGase F is known to be effective at removing glycans in Protein Deglycosylation Mix Buffers 1 and 2, 52 whereas TEAB is a known to be compatible with S-Trap sample preparation and mass spectrometry analysis. 53 To test whether a single buffer system would be compatible with both PNGase F and S-Traps, RNase B was deglycosylated using PNGase F in four different buffer conditions: the two deglycosylation buffers provided with commercially available PNGase F, TEAB, and water.…”
Section: Resultsmentioning
confidence: 99%
“…The transport of monosaccharides provides the cell with energy and metabolic precursors used for a diverse range of processes. Understanding how these sugars are transported and utilized becomes especially important since various diseases/disorders (LADII, GFUS-CDG, SLC35A2-CDG, PGM1-CDG, colitis, various cancers) are already using or exploring “monosaccharide therapy” ( 9 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%